PORTRAIT OF QURAN WAQF ACCOUNTABILITY BASED ON GORONTALO LOCAL WISDOM VALUES: A NETNOGRAPHY STUDY - Mohamad Anwar Thalib (Journal of Economic Empowerment Strategy (JEES), 2026)
This research aims to capture the practices of accountability for Quranic waqf in Gorontalo, based on local wisdom values. The religiousness paradigm is used as a basis for thinking, with a netnographic approach and qualitative methods. Data was obtained through the analysis of four YouTube videos that recorded the process of sending and distributing the Quran, along with their captions, number of views, likes, and comments. The analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The research findings indicate four forms of accountability: (1) preparation for sending the Quran to Gorontalo, (2) official handover from the Quran Waqf Agency to the local government, (3) delivery of the Quran to remote areas of Pinogu, and (4) distribution to the community and reporting on the completion of activities. This accountability practice reflects the local cultural value of Eya dila pito-pito'o, which means “God does not close His eyes,” emphasizing honesty, openness, and responsibility in every process. This finding confirms that waqf accountability is not merely an administrative report, but a manifestation of socio-religious integrity rooted in local wisdom.